Dampak Kelekatan Pada Perkembangan Tokoh Utama Dalam Cerpen Samar Pada Novel 11:11 Fiersa Besari - Etlintina Viki Verlita; Faniati Kusuma Dewi; Eva Dwi Kurniawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to analyze the attachment style experienced by the main character Samara and her father. The material object that the researcher used was a novel entitled 11:11 . The research method used is descriptive qualitative based on data sources in the short story Samar in the novel 11:11 written by Fiersa Besari. Researchers analyzed using John Bowlby's theory about attachment style. The results of the research can be concluded that the main character named Samara experiences an anxious and avoidant attachment style so that Samara finds it difficult to trust other people, feels unloved and avoids the people around her.